Integration of Critical Thinking Skill in Science Learning Using Blended Learning System in Elementary School - Prafitasari, Ferrinda; Sukarno, Sukarno; Muzzazinah, Muzzazinah (International Journal of Elementary Education, 2021)
This research aims to analyze integration of critical thinking skills in science learning using a blended learning system in elementary schools during covid-19 pandemic. Research case study qualitative with descriptive percentages. Collected data: observation, interviews, documentation, and questionnaire. Validity data: source and techniques triangulation. Data analysis techniques using Miles & Huberman: collection, reduction, presentation, and conclusions. The results of the research integration critical thinking skills in science learning using blended learning system low with (Mo<Md<Me). Mean = 14.10 is in a low category. The frequency distribution of the majority of 47.37% belongs to the low category. Percentage of indicators formulating problems 23.20%, analyzing arguments and solving problems 55.60%, evaluating 22.20%. Efforts (1) motivating ask questions during face-to-face and online learning. (2) High Order Thinking Skill (HOTS) to analyzing problems relevant daily (3) Reading books related before learning. Features WhatsApp including video calls and voice notes can be used to maximize.